Optimizing tissue microarray construction procedure to improve quality of sections. (September 2014) - Chang, Hua; Peluso, Diane; Hussain, Sadiq; Shipitsin, Michail; Blume-Jensen, Peter
Abstract : Tissue microarray (TMA) technology makes it possible to perform high throughput in situ analysis of tissue samples, and has become a powerful tool in multiple fields of life sciences. However, obtaining high-quality TMA sections can be technically challenging. In this paper, two aspects of TMA construction were investigated, namely, the paraffin type of the recipient block and the tempering method to facilitate donor core integration. Nine commonly used paraffin types were evaluated, and four were identified with satisfactory performance. It was also found that, after TMA construction, 1-hour incubation at 50°C significantly improved the integration of donor cores with the recipient block. Large TMA blocks prepared with the described method were easy to section and yielded high quality TMA slides.